FOREST PLANT INDUSTRY (HTI) IN EAST KALIMANTAN (THE ECONOMIC OUTLOOK) - Zamruddin Hasid (Journal of Economics, Business, and Accountancy Ventura, 2011)
Essentially, the implication of HTI in Indonesia and East Kalimantan province has a benefit to the front (forward) and backward for the economy. The impact to the front with the HTI will provide the raw material for the timber industry developments that affect the competi- tiveness the national timber industry through superior products from the industry are like pulp, plywood, and furniture. This paper attempts to provide information on the contribution by the forestry sector toward GDRP in the province of East Kalimantan. It also tries to see the plantation development and determine its direct influence of investment on the economic growth as well as the implication of the development. Correlation and regression analysis is adopted in analysis that is the path analysis called path coefficient. The results show that the production of forest industry is still prospective for further development. Besides that, HTI is considered productive, and in the next program, it is expected that in the future this can in- crease or improve the economy growth of the people in the area. Therefore, HTI development should be pursued so that the East Kalimantan province can focus on the development of for- estry sector. This can also in the form of encouraging the investment in such development.